TEACHERS' CORRECTIVE FEEDBACK ON STUDENTS' ORAL PRODUCTION IN EFL CLASSROOMS - Fathimah, Nida Mujahidah (2017)
Corrective feedback which requires the appropriate strategies in treating learner errors during the classroom interaction is known to give a greater impact to younger learners than to the older ones. This research paper investigated teachers' strategies in providing corrective feedback in their classrooms along with their reasons and students' perception of teachers' corrective feedback strategies in adolescent classrooms which are still rarely examined. This research involved four teachers and twelve junior high school students in two EFL classrooms in an English course in Bandung. A case study was employed in this research by conducting classroom observation through field notes and audio-video recording as well as interviews to collect the data. Based on the research findings, it was revealed that the eight corrective feedback strategies were employed during the classroom interaction. However, only the input-providing strategies, namely recasts, translation, and explicit correction were applied consistently by all teachers while the distribution of output-prompting strategies, namely elicitation, repetition, metalinguistic feedback, clarification request, and paralinguistic signal was varied among the teachers. Among those strategies, teachers preferred recasts to correct learner errors which accounted for more than a half (51%) of the total occurrences. The teachers mentioned several reasons regarding the provision of corrective feedback strategies such as type of error, learning objective and activities, as well as learner factors comprising their proficiency and affective factors. Concerning students' perception, it was revealed that most students expected their errors to be corrected through the use of explicit correction and perceived corrective feedback as a beneficial contribution for their language learning. ;